THU0349 Analysis of Real Costs of Biologic Therapy for the Treatment of Chronic Inflammatory Arthropaties in a Tertiary University Hospital. A Pilot Study. (9th June 2015) - Pego-Reigosa, J.M.; Ucha, M.; Maceiras, F.; Melero, R.; Άlvarez, M.; Mouriño, C.; Martín, A.; Rodríguez, M.; Rodríguez, M.; Balboa, V.; Uña, J.; Hernández, I.; et al.
Abstract : Background: Daily clinical practice not always corresponds with the standard use of biologic therapies (BT) in rheumatic patients.st Objectives: To determine the real vs. theoretical annual cost of BT per patient with chronic arthritis at a University tertiary Hospital. Methods: Descriptive, observational, retrospective and cross-sectional study. Information over a 5-year period (2009-2014) is collected. Inclusion criteria: a) adult patients with RA (ACR), AE (New York modified/ASAS) or PsA (CASPAR) attended at the Rheumatology Service of the University Hospital of Vigo and b) >6 months of treatment with BT. Variables: a)demographics, b)clinical, c)pharmacotherapeutic history and d)per each BT: number of dispensations, adverse events, therapeutic failures, transitory or definitive discontinuation, survival of each BT line, real and theoretical (price to retailer) annual cost/patient of each BT line. Variables are described per disease and BT. Results: 484 patients were studied (total: 755 BT lines). Mean age (years): 53.8±14.8; females: 263 (54.3%). The diseases treated were RA 226 (46.8%), AE 107 (22.2%), PsA 117 (24.2%) and other spondyloartrhopaties 33 (6.8%). Mean disease duration (years): 13.1±8.2. Mean global BT duration (months) from the beginning of the evaluation (January 2009) was: 40.9±58.9. The table shows the different BT lines used and their mean duration (months) from that date. There were 359 (47.4%) definitive withdrawals of BT, being secondary failure 156 (43.4%) and adverse events 82 (22.8%) the most frequent reasons. There were 94 (12.4%) temporal discontinuations of doses of BT. The most frequent reasons of temporal discontinuations were surgery 13 (13.8%) and non-infectious adverse events 12 (12.8%). There was modification of BT doses by optimization in 236 (31.2%) BT lines. The number (%) of patients optimized per disease was: RA 77 (34.1%), AE 35 (32.7%) and PsA 44 (37.6%). The mean duration (months) of optimization was: RA 42.0±12.7; AE 22.9±20.0 and PsA 21.9±18.2. There was modification of BT doses by intensification regimes in 24 (3.2%) of the BT lines. The number (%) of optimizations and intensifications of each BT and the mean duration (months) of optimization of the 3 more used BT are shown in the table . The mean theoretical global BT cost per year of treatment was 12, 569€ ±1, 707. The mean real global cost per year was 11, 167€ ±3, 266. The mean real and theoretical annual cost and its ratio, for the 3 more used BT are shown in the table . The mean theoretical annual cost per the 3 main diseases was: RA 12, 538€ ±1, 509; EA 12, 703€ ±1, 536 y APs 12, 647€ ±1, 165. The mean real annual cost per disease was: RA 11, 400€ ±2, 988; AE 10, 993€ ±3, 024 and PsA 10, 870€ ±2, 797. The annual real/theoretical cost ratios per disease were: 91.4, 87.6 and 86.5%, respectively. Conclusions: In daily practice there are different reasons that make that BT use differs from the standard recommendations. This makes that the real cost usually is less than the theoretical one. The detailed analysis of our data will give us relevant information about the factors that determine these variations and their involvement on the pharmaceutical cost. Disclosure of Interest: J. M. Pego-Reigosa Grant/research support from: Pfizer, M. Ucha: None declared, F. Maceiras: None declared, R. Melero: None declared, M. Άlvarez: None declared, C. Mouriño: None declared, A. Martín: None declared, M. Rodríguez: None declared, M. Rodríguez: None declared, V. Balboa: None declared, J. Uña: None declared, I. Hernández: None declared, C. Barbazán: None declared, G. Piñeiro Grant/research support from: Pfizer, N. Martínez: None declared